Mechanism of electron transfer processes photoinduced by lumazine - Denofrio, María Paula (2012)
UV-A (320–400 nm) and UV-B (280–320 nm) radiation causes damage to DNA and other biomolecules through reactions induced by different endogenous or exogenous photosensitizers. Lumazines are heterocyclic compounds present in biological systems as biosynthetic precursors and/or products of metabolic degradation. The parent and unsubstituted compound called lumazine (pteridine-2,4(1,3H)-dione; Lum) is able to act as photosensitizer through electron transfer-initiated oxidations. To get further insight into the mechanisms involved, we have studied in detail the oxidation of 2′-deoxyadenosine 5′-monophosphate (dAMP) photosensitized by Lum in aqueous solution. After UV-A or UV-B excitation of Lum and formation of its triplet excited state (³Lum*), three reaction pathways compete for the deactivation of the latter: intersystem crossing to singlet ground state, energy transfer to O₂, and electron transfer between dAMP and ³Lum* yielding the corresponding pair of radical ions (Lum˙⁻ and dAMP˙⁺). In the following step, the electron transfer from Lum˙⁻ to O₂ regenerates Lum and forms the superoxide anion (O₂˙⁻), which undergoes disproportionation into H₂O₂ and O₂. Finally dAMP˙⁺ participates in subsequent reactions to yield products.